2018
DOI: 10.1038/s41398-018-0158-y
|View full text |Cite
|
Sign up to set email alerts
|

Networks of blood proteins in the neuroimmunology of schizophrenia

Abstract: Levels of certain circulating cytokines and related immune system molecules are consistently altered in schizophrenia and related disorders. In addition to absolute analyte levels, we sought analytes in correlation networks that could be prognostic. We analyzed baseline blood plasma samples with a Luminex platform from 72 subjects meeting criteria for a psychosis clinical high-risk syndrome; 32 subjects converted to a diagnosis of psychotic disorder within two years while 40 other subjects did not. Another com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…Indeed, Weickert and colleagues have employed cluster analysis to divide patients with schizophrenia-spectrum disorders into subgroups based on elevation of multiple cytokines in unison. 27,29 They have observed that, compared with controls, a greater proportion of patients clustered within an “elevated cytokine subgroup.” Jeffries and colleagues 107 have used graph theory to examine network connectivity of blood proteins related to neuroimmunology across the psychosis spectrum, observing that protein correlation networks can successfully differentiate between controls, and prodromal individuals who transition/do not transition to psychosis. Based on the current meta-analysis, we are unable to comment on whether there is a FEP immune subgroup characterized by an abnormal immune parameter network.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Weickert and colleagues have employed cluster analysis to divide patients with schizophrenia-spectrum disorders into subgroups based on elevation of multiple cytokines in unison. 27,29 They have observed that, compared with controls, a greater proportion of patients clustered within an “elevated cytokine subgroup.” Jeffries and colleagues 107 have used graph theory to examine network connectivity of blood proteins related to neuroimmunology across the psychosis spectrum, observing that protein correlation networks can successfully differentiate between controls, and prodromal individuals who transition/do not transition to psychosis. Based on the current meta-analysis, we are unable to comment on whether there is a FEP immune subgroup characterized by an abnormal immune parameter network.…”
Section: Discussionmentioning
confidence: 99%
“…Rahimi et al [230] showed that there were no significant differences in the individual levels of MMP-9 and TIMP-1 genes in schizophrenia patients, but the MMP-9/TIMP-1 ratio was significantly altered (see also Ref. [231]). Similarly, upregulated MMP-9 serum levels were found to be strongly associated with levels of mature BDNF (MMP-9 aids in the formation of mature BDNF from pro-BDNF) in schizophrenia patients [232].…”
Section: Mmps In Schizophrenia and Bipolar Disordermentioning
confidence: 99%
“…Furthermore, the present findings are broadly in line with our findings from the previous discovery metabolomics, lipidomic, and proteomic study in the ALSPAC cohort, in which we demonstrated similar changes at 12 years of age for subjects who later went on to develop PD (22) . The findings have the potential to contribute to risk calculators for future psychotic illness and mental disorders 4 , 56 , 57 as well as to an increased understanding of psychosis and psychiatric illness as a multisystem disorder involving lipids and proteins 22 , 23 , 29 . Critically, a novelty of our study lies in the integration of proteomic and lipidomic data, specifically of the PCs and LPCs and the protein members of the complement and coagulation cascades from the same subjects.…”
Section: Discussionmentioning
confidence: 93%
“…Both the coagulation and the complement pathways have recently been highlighted in schizophrenia 57 , 73 , 74 . Our current study used the semitargeted proteomic method of DIA to extend these findings and show that upregulation of PLG within the coagulation pathway at 12 years of age is associated with later PEs.…”
Section: Discussionmentioning
confidence: 99%